HEADMASTER POLICY OF SENIOR ISLAMIC SCHOOL TO INCREAS TEACHER PROFESIONALISM AT STATE SENIOR ISLAMIC SCHOOL 2 MODEL ME - Muhammad Arifin Tanjung; Fachruddin Azmi; Syafaruddin Siahaan (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2017)
State Senior Islamic School 2 Model Medan oh of famous Islamic schools in North Sumatera. The issues in this writing are what are the formulation, organization, aplication and evaluation of headmaster Policy of Senior Islamic School to Increas Teacher Profesionalism at State Senior Islamic School 2 Model  Medan. To explain the main issue in this writings, I have to observ and intervew the moeslem population. Data has been collected will be expalined detailly and analysed by Islamic education management. Based on research, formulation of headmaster Policy of Senior Islamic School to Increas Teacher Profesionalism at State Senior Islamic School 2 Model  Medan is bottom upwhich ideas from teachers, beginning from teachers meeting in one subject, teachers meeting in one program, annual meeting in a month and annual meeting in a year, and finally in team work, for example anual teachers meeting, seminar, workshop, cofee morning, study comparation to university and other school. It will motivate teacher in teaching, activity and anythings. Besides it, headmaster facilitate everything what ever teacher need it, for example infocus, laptop and everyting. And organization of headmaster Policy of Senior Islamic School to Increas Teacher Profesionalism at State Senior Islamic School 2 Model  Medan is cooperation with school commite and he helped by vices and head program and teachers and chairman of the student. The special of school organization is an evaluation of teachers activity and relation to abroad. Headmaster states his position as the teacher who teaches students, the leader who leads teachers, a manager who manages, motivator who motivate, a supervisor who supervise teachers activity, and facilitator for teachers. And finally evaluation of headmaster Policy of Senior Islamic School to Increase the Teacher Professionalism at State Senior Islamic School 2 Model  Medan each level, beginning with teachers meeting in one subject, teachers meeting in one program, annual meeting in a month and annual meeting in a year, and finally in the team work as formulation of policy. The teachers have the responsibility of ideas and program. Key Words: Headmaster Policy, Teacher Professionalism, State Senior Islamic School 2 Model Medan